Modelagem matemática da resistência à filtração oferecida pelo bloqueio dos poros, pela camada de torta e pelo fouling irreversível em um reator anaeróbio com membrana submersa aplicado ao tratamento de águas residuárias - Esteves, Luis Felipe dos Santos (2014)
Water treatment membrane systems have several advantages in comparisonwith classical systems designed with conventional purification techniques. The filtering process is the key to success with regard to energy consumption and efficiency, enabled by optimizing the filtration using a dynamic simulation model. This study aimed to develop a mathematical model of the behavior of an anaerobic bioreactor with microfiltration membrane applied to the treatment of gray water to opti mize thei r operational performance. For both phenomena such as pore blocking, growing cakelayer and fouling were analyzed mathematically. The system used for this research was developed by the research group Center Water (Center for Bioengineering applied to Sanitation) of Environmental EngineeringDepartament, Federal University of Espírito Santo. The membrane used for the study showed intrinsic resistance to a value of 1.4 x 1012m-1. With respect to pore blocking resistance(Rp), the granulometric data provided by the manufacturer was used. These data were c ombined with the other pa rameters considered in the model, presenting resistance value of 1.52 x 1012m-1. For cake layer resistance (Rc) the results obtained in Rpwith literature data, as well as some parameters on which there was the possibility of being calculated were used.To Rc, resistanceencountered was 8.73 x 1012m-1. Finally the analysis of the behavior of the filtration, foulingresistance was simulated, with value of -1.2 x 1012m-1. All phenomena were simulated by prog ramming package Matlab / Simulink, in which an interface to generate themodel equati on was developed. The modeling showed satisfactory results within the expected limits, when compared wi th results from other surveys.